2019
DOI: 10.18485/esptoday.2019.7.1.3
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Repetition on Incidental Legal Vocabulary Learning Through Long-Term Exposure to Authentic Videos

Abstract: This study intends to identify the minimal number of repetitions needed for successful incidental learning of legal vocabulary after watching authentic videos as a leisure time activity. It also examines the effectiveness of long-term exposure to authentic videos for incidental learning of legal vocabulary. For this purpose, the participants were distributed between two groups: the incidental and the control one. The incidental group had to watch 5 hours of authentic TV documentary Forensic Files. Fourteen tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…Similar performance of the incidental and control groups, in principle, indicates that the participants from the incidental group did not acquire the target words after having watched 5 hours of the TV series. In this sense, the results of our study are in line with previous research by Bisson et al (2014), Birulés-Muntané and Soto-Faraco (2016), Peters et al (2016) and Sinyashina (2019) as the authors of these papers did not find conclusive evidence of the effectiveness of watching authentic videos for incidental learning of new lexis. At the same time, there seems to be a contradiction between the results of the present study and those by Zarei (2009), Rodger (2013), Gorjian (2014), BavaHarji et al 2014, Frumuselu et al (2015), Peters and Webb (2018), Chen et al (2018) and Pujadas and Muñoz (2019) as these studies reveal clear incidental vocabulary gains after the participants' exposure to subtitled/captioned authentic video material.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar performance of the incidental and control groups, in principle, indicates that the participants from the incidental group did not acquire the target words after having watched 5 hours of the TV series. In this sense, the results of our study are in line with previous research by Bisson et al (2014), Birulés-Muntané and Soto-Faraco (2016), Peters et al (2016) and Sinyashina (2019) as the authors of these papers did not find conclusive evidence of the effectiveness of watching authentic videos for incidental learning of new lexis. At the same time, there seems to be a contradiction between the results of the present study and those by Zarei (2009), Rodger (2013), Gorjian (2014), BavaHarji et al 2014, Frumuselu et al (2015), Peters and Webb (2018), Chen et al (2018) and Pujadas and Muñoz (2019) as these studies reveal clear incidental vocabulary gains after the participants' exposure to subtitled/captioned authentic video material.…”
Section: Discussionsupporting
confidence: 91%
“…Experiments into this matter can be divided into two groups: the ones that used short videos (maximum 1 hour) and the studies with extensive exposure to authentic audio-visual material. Studies from the first group show contradictory results: while some of them report certain vocabulary gains (Koolstra and Beentjes 1999;D'Ydewalle and Van de Poel 1999;Yuksel and Tanriverdi 2009;Peters and Webb 2018), there are also experiments that did not find conclusive evidence of the effectiveness of watching short authentic videos for new lexis learning (Bisson et al 2014;Birulés-Muntané and Soto-Faraco 2016;Peters et al 2016;Sinyashina 2019). As for the experiments from the second group, which focused on extensive exposure to authentic audio-visual material, all of them recorded vocabulary gains after the participants watched subtitled/captioned authentic videos (Zarei 2009;Rodgers 2013;Gorjian 2014;BavaHarji et al 2014;Frumuselu et al 2015;Chen et al 2018;Pujadas and Muñoz 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were tested at intervals of 30 s, 1 hr, and 24 hr by means of written cued recall. As in previous studies with manipulations during the presentation of the material (e.g., Feng et al, 2019 ; Rivera-Lares et al, 2022 ; Sinyashina, 2019 ), a substantial difference between groups was found at the initial test. The correct recall of the sentences decreased with each delay, showing forgetting.…”
Section: Discussionsupporting
confidence: 80%